An Analysis of Patient Presentations at a 2-Day Mass-participation Cycling Event: The Ride to Conquer Cancer Case Series, 2010-2012. Issue 4 (1st August 2014) - Lund, Adam; Turris, Sheila A.; Wang, Peter; Mui, Justin; Lewis, Kerrie; Gutman, Samuel J.
Abstract Objective To analyze the unique factors involved in providing medical support for a long-distance, cross-border, cycling event, and to describe patient presentations and event characteristics for the British Columbia (BC) Ride to Conquer Cancer from 2010 through 2012. Methods This study was a 3-year, descriptive case series report. Medical encounters were documented, prospectively, from 2010-2012 using an online registry. Data for event-related variables also were reported. Results Providing medical support for participants during the 2-day ride was complicated by communication challenges, weather conditions, and cross-border issues. The total number of participants for the ride increased from 2, 252 in 2010 to 2, 879 in 2011, and 3, 011 in 2012. Patient presentation rates (PPRs) of 125.66, 155.26, and 198.93 (per 1, 000 participants) were documented from 2010 through 2012. Over the course of three years, and not included in the PPR, an additional 3, 840 encounters for "self-treatment" were documented. Conclusions The Ride to Conquer Cancer Series has shown that medical coverage at multi-day, cross-national cycling events must be planned carefully to face a unique set of circumstances, including legislative issues, long-distance communication capabilities, and highly mobile participants. This combination of factors leads to potentially higher PPRs than have been reported for noncycling events. This study also illuminates the additional workload "self-treatment" visits place on the medical team. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>A</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Lund</surname> </string-name>, <string-name><given-names>SA</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Turris</surname></string-name>, <string-name><given-names>P</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Wang</surname></string-name>, <string-name><given-names>J</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Mui</surname></string-name>, <string-name><given-names>K</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Lewis</surname></string-name>, <string-name><given-names>SJ</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Gutman</surname></string-name>. An analysis of patient presentations at a 2-day mass-participation cycling event: The Ride to Conquer Cancer Case Series, 2010-2012 . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>4</issue>):<fpage>1</fpage>-<lpage>8</lpage></mixed-citation>.